DEFINITION A function f : A B is onto B (called a surjection) iff Rng(f) = B. We write f : A B to indicate that f is a surjection. Look at the illustration on page 205 and the examples on pages 206 and 207. Theorem If f : A B and g : B C, then g ◦ f : A C. That is, the composite of surjective functions is a surjection. Proof: Suppose f : A B and g : B C. By Theorem ______ we have g ◦ f : A C. Let c C. We need to show that a A such that (g ◦ f)(a) = c. onto To show that f is onto B, we can show that for any b B, there must be some a A such that f(a) = b. b B such that g(b) = c by supposition, g is onto C __________________________ a A such that f(a) = b by supposition, f is onto B __________________________ (g ◦ f)(a) = g(f(a)) = g(b) = ctwo previous lines g ◦ f : A C a A such that (g ◦ f)(a) = c onto
Theorem If f : A B, g : B C, and g ◦ f : A C, then g is onto C. That is, when the composite of two functions maps onto a set C, then the second function applied must map onto the set C. onto Proof: Suppose f : A B, g : B C, and g ◦ f : A C. Let c C. To show g is onto C, we must find b B such that g(b) = c. onto a A such that (g ◦ f)(a) = c by supposition, g ◦ f is onto C __________________________ f (a) = b for some b Bf : A B __________________________ (g ◦ f)(a) = g(f(a)) = g(b) and (g ◦ f)(a) = c two previous lines g(b) = csubstitution g : B C b B such that g(b) = c onto
DEFINITION A function f : A B is one-to-one (called an injection) iff whenever f(x) = f(y), then x = y. We write f : A B to indicate that f is an injection. 1-1 Look at the examples on pages 208 and 209. To show that f is one-to-one, we show that for any x, y A for which f(x) = f(y), we must have x = y. Theorem If f : A B and g : B C, then g ◦ f : A C. That is, the composite of injective functions is an injection. 1-1 Proof: Suppose f : A B and g : B C. To show g ◦ f is one-to-one, suppose (g ◦ f)(x) = (g ◦ f)(y). 1-1 g(f(x)) = g(f(y))change of notation f(x) = f(y) by supposition g is 1-1 __________________________ x = yby supposition f is 1-1 __________________________ g ◦ f : A C 1-1 (g ◦ f)(x) = (g ◦ f)(y) x = y
Theorem If f : A B, g : B C, and g ◦ f : A C, then f : A B. That is, if the composite of two functions is one-to-one, then the first function applied must be one-to-one. Proof: Suppose f : A B, g : B C, and g ◦ f : A C. To show f is one-to-one, suppose f(x) = f(y) for some x, y A. 1-1 g(f(x)) = g(f(y)) by supposition g is a function __________________________ (g ◦ f)(x) = (g ◦ f)(y)change of notation x = y by supposition g ◦ f is 1-1 __________________________ f : A B 1-1 f (x) = f (y) x = y
Theorem (a) Suppose f : A B and C A. Then f | C is one-to-one. That is, a restriction of a one-to-one function is one-to-one. (b) If h : A C, g : B D, and A B = , then h g : A B C D. (c) If h : A C, g : B D, A B = , and C D = , then h g : A B C D. Suppose f : A B and C A. Let f | C (x) = f | C (y) for x, y C. onto 1-1 Then f(x) = f(y).Since f is _____________, we have x = y. Proof of (a): 1-1 one-to-one Suppose h : A C, g : B D, and A B = . onto Proof of (b): h g : A B C Dh g : A B C D From Theorem ____________4.2.5 Let y C D We want to show x A B such that (h g)(x) = y. y C \/ y D ________________________________ definition of C D
Suppose h : A C, g : B D, and A B = . onto Proof of (b): h g : A B C Dh g : A B C D From Theorem ____________4.2.5 Let y C D We want to show x A B such that (h g)(x) = y. y C \/ y D _______________________ definition of C D x A such that h(x) = y _______________________ by supposition h is onto C Case 1: y C (h g)(x) = h(x) = y _______ A B = and Theorem x B such that g(x) = y _______________________ by supposition h is onto C Case 2: y D (h g)(x) = g(x) = y _______ A B = and Theorem In either case, we have (h g)(x) = y for some x A B. We have shown that in each case (h g)(x) = y for some x A B, and thus proven part (b).
Theorem (a) Suppose f : A B and C A. Then f | C is one-to-one. That is, a restriction of a one-to-one function is one-to-one. (b) If h : A C, g : B D, and A B = , then h g : A B C D. (c) If h : A C, g : B D, A B = , and C D = , then h g : A B C D. onto 1-1 Proof of (c): Suppose h : A C, g : B D, A B = , and C D = . 1-1 h g : A B C Dh g : A B C D Theorem ____________4.2.5 Suppose (h g)(x) = (h g)(y) where x, y A B. We want to show that One of the following cases must be true: (i) x, y A, (ii) x, y B,(iii) x A and y B,(iv) x B and y A.
Case (i): x, y A (h g)(x) = h(x) and (h g)(y) = h(y) Theorem ____________4.2.5 h(x) = h(y) by supposition h is 1-1 __________________________ x = y Case (ii): x, y B (h g)(x) = g(x) and (h g)(y) = g(y) Theorem ____________4.2.5 g(x) = g(y) by supposition g is 1-1_________________________ x = y Case (iii): x A and y B (h g)(x) = h(x) and (h g)(y) = g(y) Theorem ____________4.2.5 by supposition (h g)(x) = (h g)(y) __________________________ by supposition (h g)(x) = (h g)(y) __________________________ h(x) = g(y) by supposition (h g)(x) = (h g)(y) __________________________ h(x) C and g(y) D by supposition h : A C and g : B D __________________________ This is a contradiction__________________________ by supposition C D = This case is not possible; similarly, Case (iv) is not possible. We have shown that in each possible case x = y, and thus proven part (c).
1 (b) (d) Exercises 4.3 (pages )
(e) (f)
1 - continued (g) (h)
(i) (j)
1 - continued (l)
2 (b) (d)
2 - continued (e) (f)
(g) (h)
2 - continued (i) (j)
(l)
9 (a) (b)
(d)
Theorem 4.15 (a) Suppose f : A B and C A. Then f | C is one-to-one. (b) If h : A C, g : B D, and A B = , then h g : A B C D. (c) If h : A C, g : B D, A B = , and C D = , then h g : A B C D. 1-1 onto 1-1